Pengaruh Struktur Organisasi dan Budaya Organisasi Islam terhadap Efektivitas Sistem Informasi Akuntansi Manajemen - Karina Devi Nur Fitriani; Nurleli (Bandung Conference Series: Accountancy, 2023)
The rise of various cases that have occurred shows that the management accounting information system used has not been effective, that is, it has not met the characteristics of integration, flexibility, accessibility and reliability so that there is a need for transformation. One information system that effectively addresses all aspects of organization, decision making, behavior, and strategy is a management accounting information system. It is hoped that the Organizational Structure and Islamic organizational culture will be able to increase the effectiveness of the management accounting information system. The purpose of this study was to find out how much influence organizational structure and Islamic organizational culture have on the effectiveness of the management accounting information system at Islamic Commercial Banks in Bandung City. The research method used is a survey method with a quantitative approach. the data collection technique used a questionnaire in the form of a google form, the study population was Islamic commercial banks in the city of Bandung, a sample of 7 Islamic commercial banks was obtained, the observation unit was users of information systems in Islamic commercial banks, each Islamic commercial bank was given 5 questionnaires, however the return rate of the questionnaire is only 80% or as many as 40 respondents. The results of the data instrument test stated that the data were all valid and reliable. Data analysis using multiple regression. The results showed that at a significant level of 5%, organizational structure did not significantly influence the effectiveness of the management accounting information system. Meanwhile, Islamic organizational culture has a significant effect on the effectiveness of the management accounting information system at Islamic banks in the city of Bandung. Maraknya berbagai kasus yang telah terjadi menunjukkan bahwa sistem informasi akuntansi manajemen yang digunakan belum efektif, yaitu belum memenuhi karakteristik integrasi, fleksibilitas, kemudahan untuk mengakses (accessible) dan kehandalan sehingga perlu adanya transformasi. Salah satu sistem informasi yang secara efektif membahas semua aspek organisasi, pengambilan keputusan, perilaku, dan strategi adalah sistem informasi akuntansi manajemen. Diharapkan Struktur Organisasi dan budaya organisasi Islam mampu meningkatkan efektivitas system informasi akuntansi manajemen. Tujuan penelitian ini adalah untuk mengetahui seberapa besar pengaruh struktur organisasi dan budaya organisasi islam mempengaruhi efektivitas system informasi akuntansi manajemen di Bank Umum syariah Kota Bandung. Adapun metode penelitian yang digunakan adalah metode survei dengan pendekatan kuantitatif. teknik pengambilan data menggunakan kuesioner dalam bentuk google form, populasi penelitian adalah Bank umum syariah di Kota Bandung, diperoleh sampel sebanyak 7 Bank Umum Syariah, unit observasi adalah para pengguna system informasi dibank umum syariah, setiap bank umum syariah diberikan 5 buah kuesioner, akan tetapi tingkat pengembalian kuesioner hanya 80% atau sebanyak 40 responden. Hasil uji instrument data menyatakan data semua valid dan reliabel. Analisis data menggunakan multiple regresi. Hasil penelitian menunjukkan bahwa pada tingkat signifikan 5%, ternyata struktur organisasi tidak berpengaruh secara signifikan terhadap efektivitas system informasi akuntansi manajemen. Sedangkan Budaya organisasi islam berpengaruh signifikan terhadap efektivitas system informasi akuntansi manajemen di Bank umum syariah kota Bandung.